Optimization of Bandwidth Management and Network Security Using PPPoE Method and Intrusion Detection Prevention System - Muhammad Arham; Yuma Akbar (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Rural internet networks frequently struggle with unstable connections, bandwidth waste, and cyber vulnerabilities. We optimized bandwidth management and network security by implementing Point to Point Protocol over Ethernet (PPPoE) alongside Intrusion Detection and Prevention System (IDPS). PPPoE manages user authentication and dynamic bandwidth allocation, while IDPS identifies and blocks network threats. Our experimental research took place in Sukanegara Village network environment. Testing involved network load simulations and cyber-attack scenarios to evaluate system performance. We compared network metrics before and after implementation, focusing on bandwidth consumption, threat detection rates, and connection stability. PPPoE implementation reduced bandwidth consumption by 35% through controlled user access and fair distribution mechanisms. The IDPS successfully detected 92% of simulated attack attempts, including port scanning, flooding attacks, and unauthorized access attempts. Network latency dropped significantly during peak usage hours, while connection stability improved across all user categories. The combined PPPoE-IDPS solution effectively addresses rural network challenges. The system delivers cost-efficient bandwidth management while maintaining robust security protection. Implementation requires minimal additional hardware and allows management by local technical staff. Our findings support widespread adoption in community and village-scale networks seeking reliable internet infrastructure with adequate security measures.